Urban noise assessment in hospitals: measurements and mapping in the context of the city of Sorocaba, Brazil - Andrade, Erik de Lima [UNESP] (2024)
Noise pollution has become a public health problem in several countries worldwide. Noise maps are tools used in many cities, mainly on the European continent. In other regions, they are used in smaller areas, and few studies focus on hospital areas, considered noise-sensitive zones. In this context, this study aimed to perform sound measurements and noise maps for the day and night periods in the surroundings of three hospitals in Sorocaba, Brazil. Sound measurements occurred around the three hospitals based on NBR 10151 and ISO 1996 standards. The noise maps were drawn up using a calculation model based on ISO 9613–2. Results showed that the sound measurement points around the hospitals had levels above those recommended by the Brazilian standard for sensitive areas (LAeq 50 and 45 dB for day and night, respectively). The acoustic maps showed high sound levels on all faces of the hospital buildings, both during the day and at night. The worst scenario concerned the vicinity of the roads with the highest flow and speed of vehicles. We concluded that three different hospitals in the city have high sound levels in their surroundings above the recommended for sensitive areas.